2010
DOI: 10.1007/s00421-010-1647-8
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-induced effects on the neuro-mechanics of hopping in humans

Abstract: Estrogen receptors in skeletal muscle suggest a tissue-based mechanism for influencing neuromuscular control. This has important physiological implications for both eumenorrheic women with fluctuating estrogen levels and those with constant and attenuated estrogen levels, i.e., women using the monophasic oral contraceptive pill (MOCP). This study examined the effects of endogenous plasma estrogen levels on leg stiffness (K (LEG)) and foot center of pressure (COP) during hopping. Nineteen females (Age = 28.0 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…One of the potentially important unmeasured life-style confounders in this study is if our subjects were athletes or not. Although few studies show no association between being an OC user and being an athlete or between the use of OC and the extent of physical activity, [8][9][10]18 there is no clear evidence to determine if use of OC differs between athletes and the general population. Hence, we cannot rule out ''being an athlete'' as a potential unmeasured confounder in our study.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…One of the potentially important unmeasured life-style confounders in this study is if our subjects were athletes or not. Although few studies show no association between being an OC user and being an athlete or between the use of OC and the extent of physical activity, [8][9][10]18 there is no clear evidence to determine if use of OC differs between athletes and the general population. Hence, we cannot rule out ''being an athlete'' as a potential unmeasured confounder in our study.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…In this sense, the literature reports that the female physiology seems to be affected by cyclical hormonal changes arising from the menstrual cycle; in which estrogen and progesterone, in addition to the regulation of reproductive function, show actions on the central nervous system (CNS). Studies show that these sex hormones may influence on neurotransmitters such as GABA, serotonin, and glutamate, acting on membrane receptors [1][2][3] , being able to influence different brain regions with alteration of sensory perception and motor responses [4][5][6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…Interest in a hormonal role is based on our evolving understanding of the pleitropic, or multiple and varying, effects of ovarian steroids, as well as the presence of estrogen and progesterone receptors throughout the neuromusculoskeletal system [3‐5]. Whether or not gross neuromuscular control changes across the menstrual cycle remains controversial [6‐10]. Two recent studies have demonstrated changes in more basic units of neuromuscular control across the menstrual cycle, particularly the activation patterns of the vastus medialis muscle [11], as well as in the muscle stretch reflex response at the rectus femoris [12].…”
Section: Introductionmentioning
confidence: 99%